2018
DOI: 10.1371/journal.pone.0201064
|View full text |Cite
|
Sign up to set email alerts
|

Bi-frontal pneumocephalus is an independent risk factor for early postoperative agitation in adult patients admitted to intensive care unit after elective craniotomy for brain tumor: A prospective cohort study

Abstract: Postoperative agitation frequently occurs after general anesthesia and may be associated with serious consequences. However, studies in neurosurgical patients have been inadequate. We aimed to investigate the incidence and risk factors for early postoperative agitation in patients after craniotomy, specifically focusing on the association between postoperative pneumocephalus and agitation. Adult intensive care unit admitted patients after elective craniotomy under general anesthesia were consecutively enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The basic characteristics of studies were summarized in Table 1. Six studies 5,8,9,13,18,20 used Ricker sedation agitation scale, six 1,2,4,7,16,21 used Richmond agitation sedation scale (RASS), three 14,15,19 used nursing delirium screening scale (Nu‐DESC), one 17 used confusion assessment method for the intensive care unit, one 22 used a three‐point scale, and one 10 used RASS or administration of haloperidol to screen EA. Fifteen studies 1,2,4,5,7‐10,13‐18,22 reported adjusted data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic characteristics of studies were summarized in Table 1. Six studies 5,8,9,13,18,20 used Ricker sedation agitation scale, six 1,2,4,7,16,21 used Richmond agitation sedation scale (RASS), three 14,15,19 used nursing delirium screening scale (Nu‐DESC), one 17 used confusion assessment method for the intensive care unit, one 22 used a three‐point scale, and one 10 used RASS or administration of haloperidol to screen EA. Fifteen studies 1,2,4,5,7‐10,13‐18,22 reported adjusted data.…”
Section: Resultsmentioning
confidence: 99%
“…Quality evaluated by QUIPS tool (Table 2) showed 10 studies 1,2,4,5,13‐17,22 had low risk of bias of all domains, five studies 7‐9,18,21 had high risk of bias of study participation, three studies 19‐21 had high risk of adjustment for other prognostic factors and statistical analysis and reporting, and one study 10 had high risk of bias of outcome measurement and unclear risk of bias of statistical analysis and reporting. Thus, those 10 studies 1,2,4,5,13‐17,22 with low risk of bias of all domains were regarded as of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…During the study, pain, agitation and delirium were managed according to the recommendations in guidelines proposed by the European Society of Anaesthesiology and the American Society of Critical Care Medicine [ 3 , 17 ], which have been employed as routine clinical strategies in our ICU [ 13 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Postoperative analgesia was routinely administered along with patient-controlled intravenous analgesia (PCIA), which was comprised of sufentanil 100 mg and tropisetron 10 mg in 100 ml of 0.9% NaCl solution. A basal PCIA infusion (2 ml/hour) was started after confirmation of the patient’s cardiorespiratory stability and the recovery of consciousness [ 13 , 18 , 19 ]. Pain assessment was performed every 6 h or as needed using the numeric rating scale (NRS) or the Critical-Care Pain Observation Tool [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fresh frozen plasma and vitamin K were administered to those patients taking warfarin and to those whose INR was above 1.4. Continuous intravenous infusion of propofol and fentanyl was used to treat agitation [12]. We conducted a conventional glucose control scheme in our ICU.…”
Section: Methodsmentioning
confidence: 99%